Estudo e desenvolvimento de uma plataforma acessível pela web para acompanhamento de conteúdos instrucionais - Moraes Tavares de Melo, Nisston (2013)
The increasing use of virtual learning environments - VLE has made education institutions seek to benefit of the increasing possibilities that these environments offer. The structuring, control and monitoring of instructional content that is taught in the classroom or over distance are great examples and are the main subject of this work. It was developed in three phases : submission of a proposal for structuring instructional material in course plan, in such a way as to explicit the contents of each subject, their relations with the pedagogical objectives to be reached (competences and skills) and the instrumental and methodological resources which will be available in its execution; study and proposal of an informatics system architecture available in the WEB to attend, in a safe, quick and consistent way the requirements mentioned in the first phase; the implementation of an application at the level of proof of concept, instantiating the proposed architecture : System of Management and Control of Instructional Content (SGCCI). The developed application was utilized in the occurrence of a real course.